Improvement of beef cattle through breeding - Smith, W.H.; Wheat, J.D.; Spies, H.G. (Kansas Agricultural Experiment Station, 2011)
The purebred Shorthorn cattle breeding program was continued during 1964 according to the plan initiated in 1949. Inbreeding of the two lines has been continued. The Wernuere Premier Line is in its fifth generation and the Mercury line in its fourth generation of inbreeding. The inbreeding program for both lines has been basically to continue successive generations of half-sibbing.
Keywords: Beef; Inbreeding; Production traits; Inheritance